PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) MENGGUNAKAN VIDEO SCRIBE TERHADAP HASIL BELAJAR FISIKA PESERTA DIDIK KELAS X MIA SMA NEGERI 3 PAYAKUMBUH (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2020)
AbstractThis research is motivated by students' interest in learning towards on physics subject are still low and the lack of understanding of physics learning concept from the students, it causes the students do not understand about matery that has given by educators and their physics learning outomes in grade X MIA senior high shcool 3 Payakumbuh is still low. Therefore, the research conducted a research of using PBL models and video scribe media to apply in these problem. Type of this research is quasi experiment with posttest only control design. The population of this research is at X grade senior high school 3 Payakumbuh, consists of 5 class. The sampling technique is cluster random sampling, taken at X grade MIA 3 experiment and X grade MIA 5 as control class. Instruments of this research are final test used is essay with reliability of the test is r11 = 0.636. Based on the calculation results obtained th = 1.6850 with ttabel = 1.675, kareta th> ttabel, then H0 is rejected and H1 is accepted. Based on the results of the activity analyze it know that the experimental room activities is better than the physich learning outcomes of student using problem based learning (PBL) models by ussing video scribe is better than physics learning outcomes of students by using scientific learning models by using scientific learning models at X grade senior gigh school Payakumbuh.